2015
DOI: 10.1007/s00265-015-1974-1
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analysis of avian re-nesting behavior: mean, across-individual, and intra-individual responses

Abstract: Anti-predator behavior is a key aspect of life history evolution, usually studied at the population (mean), or across-individual levels. However individuals can also differ in their intra-individual (residual) variation, but to our knowledge, this has only been studied once before in free-living animals. Here we studied the distances moved and changes in nest height and concealment between successive nesting attempts of marked pairs of grey fantails (Rhipidura albiscapa) in relation to nest fate, across the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
23
1
1
Order By: Relevance
“…Ideally, such data need to also be measured in controlled conditions to negate the effect of unquantified contextual environmental variation that could affect some individuals more than others [8,9]. However, that is not to say we should not study rIIV in the field, but individual differences in rIIV will probably be hard to distinguish from responsiveness to unobserved sources of temporal or contextual variation [14,17,18]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, such data need to also be measured in controlled conditions to negate the effect of unquantified contextual environmental variation that could affect some individuals more than others [8,9]. However, that is not to say we should not study rIIV in the field, but individual differences in rIIV will probably be hard to distinguish from responsiveness to unobserved sources of temporal or contextual variation [14,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…More generally, the presence of individual variation in rIIV indicates a violation of model assumptions that can potentially affect our inferences from any data of a labile trait. Indeed, a recent study demonstrated how ignoring this level of behavioural variation altered the biological conclusions drawn from the data, severely reducing the power of the study [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Birds change their incubation patterns (Ghalambor and Martin 2002; Kovařík and Pavel 2011; Zanette et al 2011; LaManna and Martin 2016), provisioning behaviors (Ghalambor and Martin 2001; Fontaine and Martin 2006; Tilgar et al 2011; Zanette et al 2011; LaManna and Martin 2016), vigilance behavior (Morosinotto et al 2013), and nest-site selection behavior (Forstmeier and Weiss 2004; Eggers et al 2006; Peluc et al 2008; Beckmann et al 2015) in response to a change in the level of perceived risk. These studies also demonstrate that there are species-specific differences in plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…, Munro , Beckmann et al . ). Fantail pairs will build up to seven nests in one breeding season, and abandon up to 71% of their nests before egg‐laying (Beckmann et al .…”
mentioning
confidence: 97%
“…Fantail pairs will build up to seven nests in one breeding season, and abandon up to 71% of their nests before egg‐laying (Beckmann et al . ). At the population level, 40–47% of all nests are abandoned prior to laying (Munro , C. Beckmann pers.…”
mentioning
confidence: 97%